The Effect of Diabetic Foot Exercise on Peripheral Perfusion and Fall Risk in Elderly with Diabetes Mellitus: Case Report - Putri, Yuliana Eka; Sari, Sheizi Prista; Witdiawati, Witdiawati (Universitas Padjadjaran, 2025)
risk of experiencing complications such as peripheral neuropathy. Diabetic foot exercises are an intervention to control blood sugar levels and reduce the risk of complications and limited study have been found that support the intervention on the risk of further falls. This study aims to determine the effect of foot exerciseson peripheral perfusion and fall risk in elderly with DM. The research employed a case report methodology, utilizing a nursing care approach for an elderly individual aged 65 years. The client experienced peripheral neuropathy and the assessment showed that the client was in the moderate fall risk category. The intervention was given for 7 days in the morning and evening for 10–15 minutes, and evaluation was conducted daily through observation, interviews, physical examinations, and objective assessment using questionnaires Tinetti Assessment Tool. Complaints of tingling and stiffness in the feet had decreased, acral temperature became warm, CRT was 2 seconds, SpO₂ in the toes increased to 96%, GDS was 136 mg/dL, and the Tinetti Assessment Tool score was 5 with an interpretation of low fall risk. The findings of this study indicate that practicing diabetic foot exercises can improve peripheral perfusion and reduce the risk of falls in the elderly. Further research is expected to be conducted with a larger sample size and a longer intervention duration to observe its long-term effects.Keywords: Diabetic Foot Exercise, Diabetes Mellitus, Elderly